KURIKULUM AIK PADA SEKOLAH MUHAMMADIYAH DI MAGELANG: ANALISIS TERHADAP RELEVANSI DAN KENDALA - Agus Miswanto; Imam Mawardi; Lisdiana AZ (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2021)
The issue of the relevance of the curriculum to the needs of students and the handling of obstacles in implementing the curriculum in the field is one of the success factors in the education process. Therefore, this study aims to reveal the relevance and constraints of implementing the Muhammadiyah Islamic Teaching (AIK) curriculum in Muhammadiyah schools in the Magelang area. This research is a qualitative descriptive study, in which the data was collected using in-depth interviews with teachers of Muhammadiyah Islamic Teaching. Meanwhile, for data analysis using the deductive-inductive method. From this study, it was found that the Muhammadiyah Islamic Teaching curriculum, especially Islamic law, still contained material that was not relevant to the needs of students based on their taklif age, so that a review or renewal of the existing curriculum was needed. Meanwhile, in terms of implementation, there are two main obstacles to the Muhammadiyah Islamic Teaching curriculum, namely internal and external. Internally, at least three main obstacles were found, namely unbalanced curriculum time and materials, low teacher competence, and lack of facilities. To deal with these problems, each school adopts different policies depending on the problems being faced, because each school faces different levels of these problems. From the external side, the family background and social environment of students greatly affect the success of the implementation of the AIK curriculum